Assessment of the availability of essential medicines and inventory control practice at university of Gondar comprehensive specialized hospital, Amhara regional state of Ethiopia: institutional based cross-sectional study design - Woldeyohanins, Alem Endeshaw; Meseret, Bezawit; Teka, Muhabawu; Teshome, Teshale (International Journal of Scientific Reports, 2020)
Background: Assessment of availability of essential medicines is a critical component of universal health coverage and important factor to address patients’ satisfaction and increase their health seeking behavior. Proper inventory management of essential drugs in the health facilities is critical in ensuring availability of essential drugs. The objectives of the study were to assess availability of essential medicines and inventory control practice in university of Gondar comprehensive specialized hospital. Methods: The study was conducted using institution based cross sectional study design from March 10 to April 10, 2019. The data was collected by data abstraction formats and structured observation checklist and data was analyzed by Microsoft office excel for the assessment of the essential medicine’s availability and inventory control practices in Gondar university comprehensive specialized hospital. Results: The overall average availability of essential medicines during survey period in Gondar university hospital was 79.17%. The average stock out in the last six months period was 41.67%. The mean duration of stock out of essential medicines of the hospital in the last six months period was 31.7 days and average frequency of stock out was 0.7. The discrepancy between physical count and stock record count of essential medicines ranged from 0% to about 95%. Conclusions: The average availability of essential medicines during data collection period was fairly high. However, the facility was stock out for significant percent of essential medicines over the last six months period and stock out to lesser extent of percent at the time of survey period.